A Model for Agile Management of Virtual Teams for Developing Smart Environments - Mihajlović-Milićević, Jelena; Mitrović, Svetlana (E-business technologies conference proceedings, 2021)
The purpose of this article is to look at how virtual team management models are evolving in the development of smart environments. The main topic under consideration is the possibility of building a model for efficient virtual team management in the construction of smart environments utilizing the DevOps method in the SAFe framework (Scaled Agile Framework). The article will concentrate on developing and executing a virtual team management model that is specially geared to smart environment development projects. The model should make the best use of the agile methodology framework's parts and have a beneficial impact on the process of understanding, adapting, and implementing the DevOps approach in project team management. The research was conducted at the Department of E-business of the Faculty of Organizational Sciences.